Paradox of the market for the educated : a hypothesis about unemployment acting as a stimulant to private demand for higher education - Gopinathan Nair, P. R. (Parameswaran Raman), 1931- (Working paper (Centre for Development Studies (Trivandrum, India)), 1984)
In the context of Kerala, India.